2019
DOI: 10.1037/pst0000222
|View full text |Cite
|
Sign up to set email alerts
|

Examining mental health practitioners’ perceptions of clients based on social class and sexual orientation.

Abstract: There is negligible research exploring mental health clinicians' perceptions of clients based upon client social class and sexual orientation (McGarrity, 2014;Whitcomb & Walinsky, 2013). The purpose of this study was to examine how licensed mental health clinicians' perceptions of clients were influenced by a hypothetical client's social class and sexual orientation using a 2 (lower social class vs. higher social class) ϫ 2 (lesbian vs. straight) quasi-experimental vignette-based design. Results from 257 pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…It is also imperative that therapists pay close attention to their own attitudes and beliefs regarding religion or sexuality. It has been demonstrated that client characteristics (i.e., social class and sexual orientation) can inform how mental health practitioners perceive a client's anxiety, depression, and feelings about working with a particular client (see Thompson et al, 2019).…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…It is also imperative that therapists pay close attention to their own attitudes and beliefs regarding religion or sexuality. It has been demonstrated that client characteristics (i.e., social class and sexual orientation) can inform how mental health practitioners perceive a client's anxiety, depression, and feelings about working with a particular client (see Thompson et al, 2019).…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…Despite this literature, there is a scarcity of research on therapists' experiences working with clients who hold multiple cultural identities, with several notable exceptions. Thompson, Chin, and Kring (2019) conducted a quasi-experimental vignette-based study to examine therapists' perceptions of clients with various inter-This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Intersectionalitymentioning
confidence: 99%
“…Despite this literature, there is a scarcity of research on therapists’ experiences working with clients who hold multiple cultural identities, with several notable exceptions. Thompson, Chin, and Kring (2019) conducted a quasi-experimental vignette-based study to examine therapists’ perceptions of clients with various intersecting SES and sexual orientation identities. Another study evaluated how intersectionality processes emerged while working with a client who identified as an AfroLatinx, queer immigrant (Adames, Chavez-Dueñas, Sharma, & La Roche, 2018).…”
Section: Intersectionalitymentioning
confidence: 99%
“…Thus as clinicians, it is impossible to be neutral, objective, or unbiased. A large body of evidence has shown that helping professionals hold persistent implicit biases towards members of marginalized groups that contribute to disparities in diagnosis and treatment, patient ratings of the clinician, treatment adherence, and outcomes (Penner et al, 2009; Thompson et al, 2019). Due to the repetitious and unconscious nature of these thoughts and feelings, implicit biases—or “habits of the mind”—are hard to consciously change or control despite non‐prejudiced intentions (Burgess et al, 2017).…”
Section: Conceptual Foundations: Towards a Critical‐cultural‐relationmentioning
confidence: 99%